The German labor market after the Great Recession: Successful reforms and future challenges - Marco Caliendo; Jens Hogenacker (IZA Journal of European Labor Studies, 2012)
The reaction of the German labor market to the Great Recession 2008/09 was relatively mild - especially compared to other countries. The reason lies not only in the specific type of the recession - which was favorable for the German economy structure - but also in a series of labor market reforms initiated between 2002 and 2005 altering, inter alia, labor supply incentives. However, irrespective of the mild response to the Great Recession, there are a number of substantial future challenges the German labor market will soon have to face. Female labor supply still lies well below that of other countries and a massive demographic change over the next 50 years will have substantial effects on labor supply as well as the pension system. In addition, due to a skill-biased technological change over the next decades, firms will face problems of finding employees with adequate skills. The aim of this paper is threefold. First, we outline why the German labor market reacted in such a mild fashion, describe current economic trends of the labor market in light of general trends in the European Union, and reveal some of the main associated challenges. Thereafter, the paper analyzes recent reforms of the main institutional settings of the labor market which influence labor supply. Finally, based on the status quo of these institutional settings, the paper gives a brief overview of strategies to combat adequately the challenges in terms of labor supply and to ensure economic growth in the future.
Keywords: J26; J38; J68; 330; unemployment; labor force participation; labor supply; benefit systems; public policy; Wirtschaftskrise; Arbeitsmarkt; Arbeitslosigkeit; Arbeitsmarktreform; Erwerbstätigkeit; Arbeitsangebot; Alternde Bevölkerung; Fachkräfte; Deutschland